SURGICAL MANAGEMENT OF FELINE CYSTOLITHIASIS: A CASE REPORT OF BLADDER STONE REMOVAL IN A PERSIAN CAT - Dewa Ayu Sinthya Devi; I Putu Krisna Ardhia Pradnyandika; I Gusti Agung Gde Putra Pemayun (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Bladder calculi (cystolithiasis) may cause dysuria, pollakiuria, and hematuria in animals. This case report aims to describe the diagnostic approach and therapeutic management of cystolithiasis in a feline patient. A 3-year-old female Persian cat (3.17 kg) presenting with stranguries and hematuria was diagnosed via ultrasonography and radiography, revealing vesical calculi with a fausta prognosis. Surgical management through cystotomy was performed, followed by postoperative therapy including intravenous cefotaxime, subcutaneous meloxicam, and subsequent oral cefixime, meloxicam, and Kejibeling extract to prevent urolith recurrence. Clinical improvement was observed within 8 days postoperatively, evidenced by normal micturition without hematuria or discomfort. Combined surgical and medical intervention proved effective for resolving cystolithiasis in this case. Long-term monitoring and dietary modification are advised to minimize recurrence risk.